Drivers of Firm-Level Productivity in Russia's Manufacturing Sector - Bogetić, Željko; Olusi, Olasupo (World Bank, Washington, DC, 2013)
This note presents the results of an empirical analysis of firm-level productivity growth in Russia's manufacturing sector during the period 2003-08 using a rich Amadeus database as well as the recent EBRD/World Bank Business Enterprise and Performance surveys (BEEPs). The results show that productivity grew steadily between 2003 and 2008, with an annual growth rate averaging 4 percent over the period, showing no signs of a slowdown from the previous period after the 1998 crisis. Firm characteristics such as size, location, age, and the structure of firm ownership are important determinants of productivity, as evidenced by positive effects of scale economies (large firm effect), agglomeration (Moscow-city effect), private ownership, and a firm's industry dominance. Supplemental analysis of the quality of infrastructure -- water, electricity, transport, and the internet -- using BEEPS data show that infrastructure quality gaps reduce firm productivity with water supply gaps having the largest impact.